Contribution à l’étude de la cryptosporidiose chez le dromadaire dans la région sud-est Algérien - Ahmed،HAROUR (My University, 2024)
Often, neonatal diarrhea in young animals is a worrying problem for both the breeder and the veterinarian. Morbidity and mortality are high, causing considerable economic losses. The objective of this research is to estimate the frequency of the disease and its distribution according to some zootechnical parameters, to evaluate the importance of cryptosporidium spp in the onset of diarrhea in camels as well as to assess the role of infected mothers in the spread of the parasite and in the infestation of newborns. A ZIEHL-NEELSEN staining technique modified by Henriksen and Polhenz (1981) was used on 50 fecal samples, including 25 samples from camels and 25 samples from diarrheic and non-diarrheal camels taken in the Ouargla region. Microscopic observation showed that out of 50 fecal samples 09 were found to be positive for cryptosporidium spp or 18%, regarding camels 06 samples out of 25 were positive (24%) thus the frequency is higher in diarrheal camels compared to clinically diagnosed camels. healthy (20% vs 4%). The age of camels, between 2 and 3 weeks old, is the most sensitive (60%) to infestation compared to other age groups. Infected mothers included in our study can be considered a source of contamination of camels, because all positive cases of camels (3/25 or 12%) are associated with positive cases of camels. فيكثيرمنالأحيان،يشكلالإسهالعندالأطفالحديثيالولادةمشكلةمثيرةللقلقلكلمنالمربيوالطبيبالبيطري. معدلاتالإصابةوالوفياتمرتفعة، مماتسببفيخسائراقتصاديةكبيرة. الهدفمنهذاالبحثهوتقديرتكرارالمرضوتوزيعهحسببعضالمعاييرالحيوانيةوتقييمأهميةطفيليcryptosporidiumsppفيبدايةالإسهالفيالإبلوكذلكتقييمدورالأمهاتالمصاباتفيانتشارالمرض. الطفيليوفيإصابةالأطفالحديثيالولادة. تماستخدامتقنيةصبغ ZIEHL-NEELSEN المعدلةبواسطةHenriksenوPolhenz (1981) على 50 عينةبراز،بمافيذلك 25 عينةمنالإبلو25 عينةمنالإبلالمصابةبالإسهالوغيرالمصابةبالإسهالالمأخوذةمنمنطقةورقلة. أظهرتالمراقبةالمجهريةأنهمنبين 50 عينةبرازكانت 9 منهاإيجابيةلبكتيرياالكريبتوسبوريديومأو 18%،فيماكانت 06 عينةمنأصل 25 إيجابية (24%)،وبالتاليفإنالتكرارأعلىفيالإبلالمصابةبالإسهالمقارنةبالإبلالسليمةالمشخصةسريرياً (20% مقابل 4%). عمرالإبلمابين 2 إلى 3 أسابيعهوالأكثرحساسيةللإصابة (60%) مقارنةبالفئاتالعمريةالأخرى. يمكناعتبارالأمهاتالمصاباتالمشمولاتفيدراستنامصدراًلتلوثالإبل،لأنجميعالحالاتالإيجابيةللإبل (3/25 أو 12%) مرتبطةبحالاتإيجابيةللإبل. Souvent, La diarrhée néonatale des jeunes animaux constitue un problème préoccupant aussi bien pour l’éleveur que pour le vétérinaire. La morbidité et la mortalité sont élevées, engendrant des pertes économiques considérables. L’objectif de cette recherche est d’estimer la fréquence de la maladie et sa distribution selonquelques paramètres zootechnique, d’évaluer l’importance de cryptosporidiumspp dansl’installation de la diarrhée chez les chamelons ainsi pour apprécier le rôle des mères infectésdans la dissémination du parasite et dans d’infestation des nouveau-nés. Une technique de coloration de ZIEHL-NEELSEN modifié par Henriksen et Polhenz (1981) a étéutilisée sur 50 prélèvements fécaux, dont 25 échantillons des chamelles et 25 prélèvementsdes chamelons diarrhéiques et non diarrhéiques prélever a la région de Ouargla . L’observation microscopique a montré que sur 50 prélèvements de fèces 09 sont révéléspositifs au cryptosporidiumspp soit 18%, concernant les chamelons 06 prélèvements sur 25 étaientpositifs (24%) ainsi la fréquence est plus élevée chez les chamelons diarrhéiquescomparativement aux chamelons cliniquement sains (20% vs 4%). L’âge des chamelonscompris entre 2 et 3 semaine est la plus sensible (60%) à l’infestation par apport les autrestranches d’âge. Les mères infectées incluant dans notre étude peuvent être considéré comme une source decontamination des chamelons , car tous les cas positifs des chamelles (3/25 soit 12%) sontassociés aux cas positifs de ses chamelons .
Keywords: cryptosporidium spp; ZIEHL-NEELSEN; protozoa; camels; diarrhea. Ouargla...; cryptosporidiumspp،ZIEHL-NEELSEN،البروتوزوا،الجمال،الإسهال. ورقلة; cryptosporidiumspp; protozoaire; chamelons; diarrhée. Ouargla